2019
DOI: 10.1111/ejh.13332
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CD34+ cell dose on reduced intensity conditioning regimen haploidentical hematopoietic stem cell transplantation

Abstract: Objectives Haploidentical hematopoietic stem cell transplant (haplo‐SCT) has been associated with higher rates of graft rejection, and a higher dose of CD34+ cell dose is frequently requested. We aim to explore the impact of CD34+ cell dose in peripheral blood stem cell (PBSC) grafts using reduced intensity conditioning (RIC) in haplo‐SCT. Methods Sixty‐eight consecutive haplo‐SCT in adult patients were included. Graft‐vs‐host disease (GVHD) prophylaxis consisted on ATG, PTCy, and CsA. The cohort was divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…As an example, mice are lymphocyte predominant amongst the total leukocyte population while humans have a higher population of polymorphonuclear cells. 61 In humans, studies have investigated varying doses of CD34 + cells in multiple contexts and patient populations 62-64 with variable results, ultimately demonstrating that the optimal cell dose is heavily dependent on the donor and the stem cell source. 62…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, mice are lymphocyte predominant amongst the total leukocyte population while humans have a higher population of polymorphonuclear cells. 61 In humans, studies have investigated varying doses of CD34 + cells in multiple contexts and patient populations 62-64 with variable results, ultimately demonstrating that the optimal cell dose is heavily dependent on the donor and the stem cell source. 62…”
Section: Discussionmentioning
confidence: 99%
“…As an example, mice are lymphocyte predominant amongst the total leukocyte population while humans have a higher population of polymorphonuclear cells. 61 In humans, studies have investigated varying doses of CD34 + cells in multiple contexts and patient populations [62][63][64] with variable results, ultimately demonstrating that the optimal cell dose is heavily dependent on the donor and the stem cell source. 62 Rather than informing future dose levels in humans, the pertinence of murine toxicology studies is mostly related to identifying the interaction of gene edited human cells in various organs and confirming that malignancies do not develop over the observation period.…”
Section: Future Outlookmentioning
confidence: 99%
“…Our results highlight the favorable effect of higher CD34 dose on post-transplant survival in MF, and the impact of pre-transplant JAKi of our knowledge on this aspect specifically in the MF transplant setting. [28][29][30] For RFS a significant interaction between the effects of CD34 cell dose and GVHD prophylaxis regimen (use of ATG-PTCy) was found on UVA (P =.04) and MVA (Table 3). The association of CD34 dose on RFS was seen mainly in patients who had received ATG/PTCy for GVHD prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Haematopoietic reconstitution is a key issue for successful allo‐HSCT 1 . A number of studies reported by others and have delineated the association of a higher CD34 + cell dose in allografts with faster haematopoietic recovery 2–6 and better survival, 7–12 although a few researchers failed to demonstrate this association 13,14 . The above‐mentioned controversy might be related to the differences in underlying disease, conditioning regimen, and graft‐versus‐host disease (GVHD) prophylaxis of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…1 A number of studies reported by others and have delineated the association of a higher CD34 + cell dose in allografts with faster haematopoietic recovery [2][3][4][5][6] and better survival, [7][8][9][10][11][12] although a few researchers failed to demonstrate this association. 13,14 The abovementioned controversy might be related to the differences in underlying disease, conditioning regimen, and graft-versus-host disease (GVHD) prophylaxis of these studies. Thus, further studies are needed to elucidate the effects of CD34 + cell dose in patients with homogeneous underlying disease and other clinical characteristics.…”
Section: Introductionmentioning
confidence: 99%